Exploring the Shift From HIV Pre-exposure Prophylaxis Awareness to Uptake Among Young Gay and Bisexual Men - Koester, Kimberly A.; Erguera, Xavier A.; Udoh, Ifeoma; Kang Dufour, Mi-Suk; Burack, Jeffrey H.; Myers, Janet J. (Frontiers in Public Health, 2021)
Introduction: HIV pre-exposure prophylaxis (PrEP) in the form of a daily oral medication is highly effective at preventing HIV. In the United States, awareness about PrEP has steadily increased over time among individuals vulnerable to HIV, however awareness has not translated into widescale uptake. Estimates are that fewer than 20% of 1.2 million Americans for whom PrEP is indicated are utilizing it. We sought to understand how individuals moved from PrEP awareness to PrEP utilization. Methods: We conducted a series (n = 31) of in-depth interviews with young people, predominantly gay and bisexual men, ages 18–29 years old between February 2015 and January 2016, as part of the evaluation of a multi-year demonstration project funded to test innovative approaches to improve sexual health outcomes and curb the HIV epidemic in California. Interviews were audio-recorded and transcribed verbatim. We conducted a thematic analysis. Results: We present a continuum of PrEP awareness that spans three phases—basic, moderate and advanced. Participants rarely reported becoming well-informed about PrEP over the course of an initial exposure to PrEP information. Learning occurred after multiple exposures to PrEP information through numerous intersecting forms, messengers and formal and informal communication channels. Positively framed messages delivered by formal messengers emphasizing PrEP as a sensible HIV prevention strategy and explicitly communicating a regard for sexual wellness were overwhelmingly persuasive and facilitated movement to the advanced awareness phase. Once participants reached the advanced phase of PrEP awareness, uptake was possible. Conclusions: Our analysis provides insights into how PrEP awareness led to PrEP uptake among young gay and bi-sexual men. Building demand among those in the basic awareness phase took longer than those in the moderate phase. Individuals involved in formal and informal PrEP education can set reasonable expectations about whether, when and how eventual uptake may occur when keeping the continuum of PrEP awareness framework in mind. Many young, gay and bi-sexual male prospective PrEP users will benefit from positively framed messages that emphasize personal well-being, including social, sexual and emotional benefits of PrEP use.